Loss analysis and optimization of PV module components and design to achieve higher energy yield and longer service life in desert regions. (15th December 2020) - Hanifi, Hamed; Pander, Matthias; Zeller, Ulli; Ilse, Klemens; Dassler, David; Mirza, Mark; Bahattab, Mohammed A.; Jaeckel, Bengt; Hagendorf, Christian; Ebert, Matthias; Gottschalg, Ralph; Schneider, Jens
Graphical abstract: Highlights: Optimization of power, durability, and performance of PV modules for desert areas. 9.58% gain in efficiency by proper choice of materials and module design. Encapsulant suggestions to reduce UV degradation on front and rear side of PV cells. Reduction of cell movement due to the temperature cycles and risk of tab breakage. Up to 35% reduced soiling losses by using a new anti-soiling coating. Abstract: The global share of photovoltaic plants in desert locations increases continuously due to inexpensive land and higher yield due to higher irradiation levels. However, PV modules suffer from harsh environmental conditions that influence their lifetime and, consequently, the levelized cost of electricity. Environmental factors such as high temperature differences between nights and days, high ultraviolet doses, high ambient temperatures, and high airborne dust lead to durability and performance issues such as delamination, discoloration, fatigue of interconnection, breakage of solar cells, hot-spots, and power loss due to the soiling. In this work, different bills of materials and module designs are evaluated, targeting optimum PV output power while increasing the service life and performance of the PV modules in desert climates. A stepwise optimization of module components (solar cells, glass coating and polymers/encapsulation) and module design (full vs. half cells, tab widths) are performed by simulation and experimental approaches. Simulations results analyzes the loss mechanisms and electricity production of PV modules by considering the impact of module material and design Experimentally, ultraviolet stress tests and thermal cycling tests are performed for polymer durability and interconnection fatigue analysis. The soiling reduction potential of a newly developed glass coating is investigated by outdoor exposure tests in Saudi-Arabia. It is shown by proper choice of materials and optimized interconnection design, the efficiency of the module is increased by 9.58%rel. relative to the reference module. Furthermore, the choice of encapsulant and module design strongly affect the expected service-life, and soiling losses could be reduced up to 35%.